AsiaSim 2014 14th International Conference on Systems Simulation, Kitakyushu, Japan, October 26-30, 2014. Proceedings - Tanaka, Satoshi; Hasegawa, Kyoko; Xu, Rui.; Sakamoto, Naohisa; Turner, Stephen John.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 14th International Conference on Systems Simulation, Asia Simulation 2014, held in Kitakyushu, Japan, in October 2014. The 32 revised full papers presented were carefully reviewed and selected from 69 submissions. The papers are organized in topical sections on modeling and simulation technology; network simulation; high performance computing and cloud simulation; numerical simulation and visualization; simulation of instrumentation and control application; simulation technology in diversified higher education; general purpose simulation.
Modeling and simulation technology -- Network simulation -- High performance computing and cloud simulation -- Numerical simulation and visualization -- Simulation of instrumentation and control application -- Simulation technology in diversified higher education -- General purpose simulation.
Keywords: Computer science; Computer system failures; Algorithms; Computers; Computer simulation; Computer Science; Simulation and Modeling; Models and Principles; Algorithm Analysis and Problem Complexity; System Performance and Evaluation; Electronic books